Aggregated Modelling Analysis Of Power Flow From Wind Power Plant Into Grid System Using MATLAB/ SIMULINK Software - Ahmed Al-Kaiali, Suhaib Salam Mohammed; Omar, Rosli; Sulaiman, Marizan; Al-Hiealy, Mohammed Rasheed Jubair (Asian Research Publishing Network (ARPN), 2018)
In consistent with the growth in demand, complexity of electric power systems has evolved to meet the requirements of supply. Power is generated from non-renewable, fossil fuels and nuclear fuel while renewable energy resources mainly include solar and wind. Power from Wind plants WP has shown a fast growth in the last decades due to their economic benefits especially at areas with the proper wind speed and the possibility to connect wind generators in distribution or transmission power networks. Conventional power unit generators are of high generation capacities, therefore smaller numbers are required in power plant, in other hand wind turbines WP are of smaller capacities therefore, Wind Power Plants (WPPs) consist of dozens or hundreds of low-power units. Time domain simulations of WPPs may take too much time if detailed models are considered in such studies while reduced order models used in interconnection studies of synchronous machines with full converter technology significantly reduce computational time (1, 2). The performance of all models is evaluated based on time domain simulations in the Simulink/MATLAB environment. The work includes the simulation of 50 MW WPP constructed from 18 MW doubly fed induction generators (DFIGs) aggregated (reduced) to one system of Nx2.78 MW generation capacity interconnected to existing conventional system network through 132 kV grid. The analysis includes active and power flow at the farm and the PCC terminals also power flow at PCC has been assessed for different level of WP penetration. Outputs from the MATLAB/SIMULINK modeling and simulation introduces the level of the grid voltage, current active and reactive power in the PCC and the wind farm terminal.